If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3 = 8 + 4x Reorder the terms: -3 + 5x = 8 + 4x Solving -3 + 5x = 8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -3 + 5x + -4x = 8 + 4x + -4x Combine like terms: 5x + -4x = 1x -3 + 1x = 8 + 4x + -4x Combine like terms: 4x + -4x = 0 -3 + 1x = 8 + 0 -3 + 1x = 8 Add '3' to each side of the equation. -3 + 3 + 1x = 8 + 3 Combine like terms: -3 + 3 = 0 0 + 1x = 8 + 3 1x = 8 + 3 Combine like terms: 8 + 3 = 11 1x = 11 Divide each side by '1'. x = 11 Simplifying x = 11
| (x/17)=4 | | x^2/3+2x=1+x | | 6y+2(y-4)=4(y+1)-3 | | (x/17)=2 | | -29=-5b+6 | | (-x/10)=3 | | 5(x-1)-8=2x+3(-3+x) | | -20=10+6r | | x^2/5-3x^1/5+2=0 | | X/9-6=-5 | | -4y-9=2y+9 | | 9+n/6=8 | | 6(8-z)/5=-z | | m^2=6m-10 | | 3-2r=-35 | | 5x*2+9x-9=4 | | 5-5x=-70 | | -22=p-3 | | -4(5x-2)+9=-20x+17 | | 8p=-10p+36 | | Y+4/7=-3 | | 6(4x-2)=24x-12 | | 4x^2+9y^2+8x+18y-83=0 | | 2x^2/3+x^1/2-1=0 | | 2X^2-21X+90=0 | | (13x+20)=(10x+27) | | 5(z+5)=0.8(z+3) | | 2/x-2=5/2x-1 | | 2/x-2=572x-1 | | logx^2=-5.13 | | x^2-15=110 | | =3AB-27B-A+9 |